2015
DOI: 10.1007/978-3-319-18914-7_32
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Approach to Prediction of Exacerbations of Chronic Obstructive Pulmonary Disease

Abstract: Abstract. Chronic Obstructive Pulmonary Disease (COPD) places an enormous burden on the health care systems and causes diminished health related quality of life. The highest proportion of human and economic cost is associated to admissions for acute exacerbation of respiratory symptoms. The remote monitoring of COPD patients with the view of early detection of acute exacerbation of COPD (AECOPD) is one of the goals of the respiratory community. In this study, machine learning was used to develop predictive mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Another study remotely monitored AECOPD in patients via questionnaire data. They demonstrated an accuracy of 100% for event-based prediction and up to 80.5% for symptom-based prediction [ 23 ]. In addition, Shah et al [ 24 ] used pulse oximetry and three vital signs to predict AECOPD, reaching a mean AUROC of 68%.…”
Section: Discussionmentioning
confidence: 99%
“…Another study remotely monitored AECOPD in patients via questionnaire data. They demonstrated an accuracy of 100% for event-based prediction and up to 80.5% for symptom-based prediction [ 23 ]. In addition, Shah et al [ 24 ] used pulse oximetry and three vital signs to predict AECOPD, reaching a mean AUROC of 68%.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in the development of more accurate predictive algorithms using machine learning is increasing; Sanchez-Morillo and colleagues [ 41 ] in a recent review concluded that, while some of these show promise, they have been based on relatively small numbers of patients and events [ 42 , 43 ]. They require validation in larger samples of patients, for longer periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…With the exceptions of the studies by Fernandez-Granero et al 23,24 which present a special case of predictive model based on respiratory sounds recorded for six months with an ad-hoc designed electronic sensor, and with the exception of Mohktar et al, 26 who themselves point out the issues related to small sample sizes in respiratory-related telehealth research, the size of all the datasets shown in Table 1 is large and varies from 7823 to 67 subjects.…”
Section: Introductionmentioning
confidence: 99%